2017
DOI: 10.1038/srep39852
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Improving Process for the 3D Printed Structure

Abstract: The authors focus on the Fused Deposition Modeling (FDM) 3D printer because the FDM 3D printer can print the utility resin material. It can print with low cost and therefore it is the most suitable for home 3D printer. The FDM 3D printer has the problem that it produces layer grooves on the surface of the 3D printed structure. Therefore the authors developed the 3D-Chemical Melting Finishing (3D-CMF) for removing layer grooves. In this method, a pen-style device is filled with a chemical able to dissolve the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 35 publications
1
66
0
Order By: Relevance
“…Kensuke et al observed that in three‐dimensional printing with fused deposition modeling technique, grooves and cracks were generated in the surface layer after supports removal resulting in poor appearance, poor part adaptation and some dimensional inaccuracies due to postprocessing and polishing of the surface that makes slight alteration of the model surface geometry. So, printing supports were designed to be toward the guide convex surface not the concave surface which was supposed to fit and adapt on the skull cap …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kensuke et al observed that in three‐dimensional printing with fused deposition modeling technique, grooves and cracks were generated in the surface layer after supports removal resulting in poor appearance, poor part adaptation and some dimensional inaccuracies due to postprocessing and polishing of the surface that makes slight alteration of the model surface geometry. So, printing supports were designed to be toward the guide convex surface not the concave surface which was supposed to fit and adapt on the skull cap …”
Section: Discussionmentioning
confidence: 99%
“…So, printing supports were designed to be toward the guide convex surface not the concave surface which was supposed to fit and adapt on the skull cap. 33 Athanasiou et al noticed that poly(lactic acid)-poly(glycolic acid) polymers, in addition to being susceptible to damage by moisture and radiation, are heat sensitive because of their thermoplastic nature, so cold sterilization was considered for the guide sterilization before surgery. 34…”
Section: Discussionmentioning
confidence: 99%
“…Polymers for photopolymerization offer the curing of low/high viscosity, thin/thick films in the violet to red light (light emitting diodes [LEDs] or laser diodes) with wavelength range (360–660 nm), under air, and even under low light intensity sources (e.g., halogen lamp, sun, fluorescent lamp) . Photopolymerization in general includes steps of photoinduced free‐radical polymerization (FRP), cationic‐catalyzed polymerization (CP) and anionic‐catalyzed polymerization (AP), free‐radical‐promoted CP, thiol‐ene polymerization, redox polymerization, and controlled polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION Polymers for photopolymerization offer the curing of low/high viscosity, thin/thick films in the violet to red light (light emitting diodes [LEDs] or laser diodes) with wavelength range (360-660 nm), under air, and even under low light intensity sources (e.g., halogen lamp, sun, fluorescent lamp). [1][2][3][4][5][6] Photopolymerization in general includes steps of photoinduced free-radical polymerization (FRP), cationic-catalyzed polymerization (CP) and anionic-catalyzed polymerization (AP), free-radical-promoted CP, thiol-ene polymerization, redox polymerization, and controlled polymerization. 2,7 Controlled polymerization requires the presence of a photoinitiator (PI), photosensitizer (PS), or a multicomponent photoinitiating system, for example, PI/hydrogen donor, PI/electron donor, PS/PI, or PI/PS/additive, which generate radicals, acids, radical cations, and/or photobases.…”
mentioning
confidence: 99%
“…In a typical commercial pipette the piston is made to be gas-tight with a gasketed plunger inside a smooth barrel. Consumer grade fused deposition modeling (FDM) printers are unable to build a smooth surface do to the formation of ridges that occur as each layer is deposited 44 . The ridges formed by FDM make it impractical to form a gas-tight seal between moving parts, even with a gasket.…”
Section: Introductionmentioning
confidence: 99%